Colonial Nature: Hunting in Karen Blixen’s "Out of Africa" - Larsen, Laura Soland Wang (Culture and History: Student Research Papers, 2024)
This article examines the hunting practices in the British colonies, the significance of hunting and what the specific hunting style used, revealed about the imperial and colonial mindset of that time. Furthermore, this article examines the gendered and racial aspects of colonial life and hunting, as well as the personal hunting experiences of the Danish author Karen Blixen. This article argues that hunting in the British colonies was a significant part of colonial life and imperial control, as well as a great influence on the gender ideals and roles of this time. The personal experiences of Karen Blixen as settler, white, woman and hunter functions as an embodiment of the colonial and imperial views of this time and place.